Actualization of Democratic Values as Resolution of Interreligious Conflict in the Village - Silkania Swarizona; Mohammad Darry Abbiyyu; Bambang Sigit widodo; Ahmad Nizar Hilmi; Iman Pasu Marganda; Agung Stiawan (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
Studies regarding the actualization of democratic values ​​at the village level are generally a factor in the emergence of horizontal conflicts that occur in village communities. However, this article explains that the actualization of democratic values ​​actually led to conflict resolution involving fellow religious believers in Watutulis Village, Prambon District, Sidoarjo Regency. The data findings show that learning, understanding and implementing democratic values ​​has an impact on the importance of living with differences and provides space for freedom for every religious adherent to carry out their worship. To obtain in-depth data, research was carried out by interviewing religious leaders involved in the conflict, village officials, then observing religious activities, and collecting documents from related parties. In efforts to carry out conflict resolution, all parties agree on a dialogue process which then agrees on the values ​​of democracy, namely respect for the freedom of individuals or groups to express their beliefs, equal status before the law and community participation in the context of village development. The argument of this article is that the implementation of democratic values ​​at the village level can work and actually become the foundation for the development of a modern democratic society. Understanding democratic values ​​such as respect for human rights actually makes efforts to resolve horizontal conflicts between religious communities in the village.